"Hojum" Movement in Uzbekistan: Purpose and Consequences - Yakhshiyev Anvar Jurakulovich (Scientific Trends, 2025)
This article explores the "Hujum" movement that emerged in Uzbekistan. It examines the historical origins, core objectives, socio-political activities, and the broader impact and consequences of the movement within the country. The study also investigates public perception and governmental response. Through scholarly analysis, the paper evaluates the role of the movement in Uzbekistan's political landscape.
Keywords: Hujum movement, Uzbekistan, political movements, activism, social impact, historical analysis.